Critical Sociocybernetics: Developing the Concept of Dispositif for an Analysis of Steering Processes Between Social Systems - Barrón Pastor, Juan Carlos; Cardiel Herrera, Jorge (Journal of Sociocybernetics, 2018)
Sociocybernetics is particularly interested in investigating how societies steer their social systems. According to Hornung (2006), sociocybernetic studies have predominantly followed three main strategies: a problem–solution scheme, a structural analysis and a normative proposal. We consider that, to have an integral constructivist foundation, sociocybernetics needs to also take a critical perspective into account. Critical theory used to be circumscribed to the first school of Frankfurt, but now it includes a wide range of approaches —such as Michel Foucault’s genealogical and archaeological project, psychoanalytical perspectives (e.g. Slavoj Žižek), schizoid-analysis (e.g. Gilles Deleuze and Felix Guattari), feminist perspectives (e.g. Judith Butler), and de–colonialist proposals (e.g. Boaventura De Sousa Santos)— offering very diverse notions of power, ethics and transformation. Nevertheless, some key concepts, such as dispositif, event, subject, cultural industry and antagonism, link many of these critical theorists. In this article, we explore how sociocybernetics can develop a critical perspective and some of the challenges of bringing together concepts pertaining to different theories. Specifically, we develop the concept of dispositif originally used by Foucault, Agamben and Deleuze for an analysis of asymmetrical dynamics of power and steering processes between social systems. Thus, we put forth a sociocybernetical understanding of dispositifs as second–order steering mechanisms which intervene strategically between systems and couple them conditionally. Ultimately, we seek to demonstrate that sociocybernetics can benefit from critical theory and vice versa.